The Influence of the Talking Stick Cooperative Learning Model on Science Learning Outcomes Theme 6 Subtheme 3 in Class V Students at SDN 107400 Bandar Khalipah - Robenhart Tamba; Effriana Febiyanti Sihaloho; Tri Wahyu Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine whether there is an effect of using the Talking Stick type Cooperative learning model on learning outcomes in science theme 6 Sub-theme 3 PB 1 in Class V students at SDN 107400 Bandar Khalipah. The sample of this study was class V SDN 107400 Bandar Khalipah which consisted of 2 classes, namely 24 students from the experimental class and 20 students from the control class. This research method is an experimental type of Quasy Experiment Design. The results showed that the learning outcomes using the Talking Stick model were higher than the learning outcomes of students using the conventional model. The results of the statistical test showed that the learning outcomes of students using the Cooperative Talking Stick type model were 47.83 in the pretest and 83.08 in the posttest, while the learning outcomes using the conventional model were 54.4 in the pretest and 66.2 in the posttest. Technical analysis of research data using the t-test formula. The results of the hypothesis prove that t count > t table or 5.136 > 2.081 at a significant level α = 0.05. so it can be concluded that Ho is rejected Ha is accepted. This means that there is a significant influence from the use of the Talking Stick cooperative learning model on student learning outcomes in the science content, theme 6, sub-theme 3 in fifth grade students at SDN 107400 Bandar Khalipah.